The role of selenium and catechin on relation between lead toxicity and trace elements in testis tissue - ÖZDEMİR, Semra; DURSUN, Şefik (Cerrahpaşa Medical Journal, 2019)
Lead is one of the toxic and carcinogenic heavy metal for organism. Being exposed to the metal especially is realized via environmental pollution and their wide range usage in industrial field. The present study was planned to determine the possible effects of lead on of trace elements concentrations in testis tissue and. protective roles of selenium and +(-) catechin against the toxic effects of lead. The study has been performed in Wistar Albino type rats which divided into four groups as control, lead, lead+selenium and lead+catechin received groups. The experimental groups have received lead acetate, sodium selenite and +(-) catechin via their drinking water for thirty days. Besides lead as heavy metal and trace element concentrations and were performed in testis tissue of rats. In the plasma lipid peroxidation measurements were also performed. The accumulation of the lead was observed in testis tissue during experimental period. In the testis tissue of lead and lead+catechin applied groups, an increased lipid peroxidation was observed. In all other group testis tissue weights found to be lightened compare to control group. Selenium applied group trace element concentrations were found to be about showed no change when compared to controls but in catechin applied group no such a result has been detected. As a result of present study it may be concluded that; in determination of lead toxicity, malondialdehyde measurements have to be evaluated besides measurements of tissue element concentration. And administration of selenium may be helpful against the toxic effect of lead in tissue.